Government capacity, societal trust or party preferences: what accounts for the variety of national policy responses to the COVID-19 pandemic in Europe?. Issue 7 (3rd July 2022) - Toshkov, Dimiter; Carroll, Brendan; Yesilkagit, Kutsal
ABSTRACT: European states responded to the rapid spread of the COVID-19 pandemic in 2020 with a variety of public policy measures. In this article we ask what can account for this variation in policy responses, and we identify a number of factors related to institutions, general governance and specific health-sector related capacities, societal trust, government type, and party preferences as possible determinants. Using multivariate regression and survival analysis, we model the speed with which school closures and national lockdowns were imposed. The models suggest a number of significant and often counterintuitive relationships: more centralized countries with lower government effectiveness, freedom and societal trust, but with separate ministries of health and health ministers with medical background acted faster and more decisively. High perceived capacity might have provided false confidence to the governments, resulting in a delayed response to the early stages of the pandemic. Furthermore, more right-wing and authoritarian governments responded faster.